2013
DOI: 10.1073/pnas.1302546110
|View full text |Cite
|
Sign up to set email alerts
|

Essential role of stress hormone signaling in cardiomyocytes for the prevention of heart disease

Abstract: Significance Stress is increasingly associated with heart disease. Glucocorticoids are primary stress hormones, yet their direct role in the heart is poorly understood. Mice lacking the glucocorticoid receptor specifically in cardiomyocytes die prematurely from heart failure. The deficiency in glucocorticoid signaling leads to the aberrant regulation of a large cohort of genes strongly associated with both cardiovascular and inflammatory disease processes. These findings reveal an obligate role for c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

7
116
1
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 110 publications
(125 citation statements)
references
References 22 publications
7
116
1
1
Order By: Relevance
“…Global gene expression analysis of the hearts of these mice revealed significant dysregulation of several gene networks associated with cardiomyocyte homeostasis and function. Among these genes, we observed two members of the Krüppel-like factor (KLF) family of transcriptional regulators, Klf15 and Klf13 (14).…”
mentioning
confidence: 99%
See 3 more Smart Citations
“…Global gene expression analysis of the hearts of these mice revealed significant dysregulation of several gene networks associated with cardiomyocyte homeostasis and function. Among these genes, we observed two members of the Krüppel-like factor (KLF) family of transcriptional regulators, Klf15 and Klf13 (14).…”
mentioning
confidence: 99%
“…Upon ligand binding, glucocorticoid receptor translocates to the nucleus to regulate the expression of thousands of genes through direct DNA binding, by interacting with other transcription factors, and by regulation of RNA turnover (4 -6). Glucocorticoid receptors are highly expressed in heart cardiomyocytes, fibroblasts, and endothelial cells (7)(8)(9)(10)(11)(12), and several direct actions of glucocorticoids in the heart have been described in vivo (13,14). For example, Rog-Zielinska et al (13) recently demonstrated that glucocorticoid signaling in cardiomyocytes is necessary for heart maturation during development.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…In the GR deficient hearts, the expression of ryanodine receptor 2 (RyR2) is reportedly suppressed in the cardiomyocytes of GR deficiency. RyR2 is involved in abnormal calcium handling in cardiac hypertrophy and heart failure [15]. To facilitate coordinated Ca-induced Ca release, groups of RyR2 are localized in discrete areas in the sarcoplasmic reticulum (SR) membrane directly adjacent to L-type Ca channels within the Ttubules of the sarcolemma [16].…”
Section: Discussionmentioning
confidence: 99%